RELIABILITY OF THE TURNING PROCESS. MODELS IN MACHINING PROCESSES. - Nematov , Abror Akbar ugli (Educational Research in Universal Sciences, 2023)
The concept of virtual production (VP) involves reproducing a complete virtual model of the machine tool, its processes and auxiliary devices. This allows the feasibility of the process to be visualized without the use of real tests.